The m-Center Problem: Minimax Facility Location - Garfinkel, R. S.; Neebe, A. W.; Rao, M. R. (Management Science, 1977)
The m-Center Problem is to locate a given number of (emergency) facilities anywhere along a road network so as to minimize the maximum distance between these facilities and fixed demand locations assigned to them. Fundamental properties of the m-Center Problem are examined. The problem is modeled using integer programming, and is successfully attacked using a binary search technique and a combination of exact tests and heuristics. Computational results are given.